Optimizing Workplace Safety: A Comprehensive Analysis Of Accident Risks Through FMEA And RCA Methods - Permana, Muhammad Ilham; Widyaningrum, Dzakiyah (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Occupational health and safety (OHS) is the key to the company's growth in modern industry. Awareness of OHS has a positive impact on employees financially and non-financially. Indifference to OHS can be fatal, causing harm. OHS includes the establishment of a safe work environment through various approaches. Work accident data at PT. XYZ reaches 36% of the workforce, not yet meeting the government's zero accident policy—workshop at PT. XYZ has 9 types of OHS Risk. This study will use an assessment method using the Failure Mode and Effect Analysis (FMEA) method. After identifying and assessing these risks, improvement proposals will be made using Root Cause Analysis (RCA). Judging from the risks that need to be overcome immediately from the RPN value obtained, namely operating a gas-cutting machine with a value of 71.94, the eye is exposed to iron splashes during the turning process with a value of 64.51. Finally, interference with the eye during the welding process with a value of 60.11 is broken down through the RCA method to find the root cause of the problem. Then, a proposal for improvement is made.Keywords: FMEA, OHS, PPE, Risk, RPN, RCA